2021
DOI: 10.30757/alea.v18-67
|View full text |Cite
|
Sign up to set email alerts
|

Parking on supercritical Galton-Watson tree

Abstract: At each site of a supercritical Galton-Watson tree place a parking spot which can accommodate one car. Initially, an independent and identically distributed number of cars arrive at each vertex. Cars proceed towards the root in discrete time and park in the first available spot they arrive at. Let X be the total number of cars that arrive at the root. Goldschmidt and Przykucki proved that X undergoes a phase transition from being finite to infinite almost surely as the mean number of cars arriving to each vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…They were interested in these dynamics because of a connection to a spin glass model. For the usual parking process Bahl, Barnet, and Junge demonstrated through an example on d-ary trees that the phase state depends on more than just the mean initial density of particles [BBJ21,Proposition 7]. In an attempt to qualitatively describe this phenomenon [BBJ21, Theorem 8] further showed that the total number of visits to the root increases when the underlying placement of A-particles is made more volatile.…”
Section: Introductionmentioning
confidence: 99%
“…They were interested in these dynamics because of a connection to a spin glass model. For the usual parking process Bahl, Barnet, and Junge demonstrated through an example on d-ary trees that the phase state depends on more than just the mean initial density of particles [BBJ21,Proposition 7]. In an attempt to qualitatively describe this phenomenon [BBJ21, Theorem 8] further showed that the total number of visits to the root increases when the underlying placement of A-particles is made more volatile.…”
Section: Introductionmentioning
confidence: 99%